Manual for environmental health contingency planning and rapid needs assessment for floods in the Caribbean (CEHI CastriesLC, 2003)
Outlines guidelines for environmental health contingency planning for floods. Provides during and post flood needs assessment tools for Environmental Health Units.
Keywords: ENVIRONMENTAL HEALTH